2007
DOI: 10.1002/hrm.20157
|View full text |Cite
|
Sign up to set email alerts
|

Bias against overweight job applicants: Further explorations of when and why

Abstract: H Hu um ma an n R Re es so ou ur rc ce e M Ma an na ag ge em me en nt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 34 publications
3
72
0
4
Order By: Relevance
“…It is not surprising, then, that research on the stigmatizer's perspective has dominated the literature, revealing the why, when, and consistency across situations in which stigmatizers feel negatively toward heavy targets [e.g. 12,22,37,44]. In fact, two recent meta-analyses have documented that employers and managers stigmatize heavy employees and subordinates across all stages of the employment cycle [10,45].…”
Section: The Stigmatizer And/or Target Perspectivementioning
confidence: 99%
“…It is not surprising, then, that research on the stigmatizer's perspective has dominated the literature, revealing the why, when, and consistency across situations in which stigmatizers feel negatively toward heavy targets [e.g. 12,22,37,44]. In fact, two recent meta-analyses have documented that employers and managers stigmatize heavy employees and subordinates across all stages of the employment cycle [10,45].…”
Section: The Stigmatizer And/or Target Perspectivementioning
confidence: 99%
“…They examined perceptions of weight-related employment discrimination and found few race differences and no consistent trends across racial groups. Similarly, Finkelstein et al (2007) failed to find significant race effects in their weight-based discrimination experiment. Lack of significant race differences may be a function of predominantly White raters (Hebl & Heatherton, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Crandall and Martinez (1993) found lower antifat attitudes amongst Mexican-American participants. However, one experimental study examining weight-based discrimination did not find support for race as a moderator (Finkelstein, DeMuth, & Sweeney, 2007).…”
Section: Racementioning
confidence: 98%
“…However, existing research has yet to explicitly test this process model. Instead, the theory has been based on the integration 11 of research findings using group membership (e.g., male/female, normal weight/overweight) as a predictor of (a) stereotypical attributes (Crocker et al, 1993;Harris, Harris, & Bochner, 1982;Koenig, Eagly, Mitchell, & Ristikari, 2011;, and/or (b) evaluative outcomes for specific work roles (Bowen et al, 2000;Davison & Burke, 2000;Dean et al, 2008;Finkelstein et al, 2007;Roehling et al, 2013;Swim et al, 1989). In other words, research has not explicitly tested the mediational hypothesis that possessing certain characteristics (e.g., being female or overweight) leads evaluators to ascribe stereotypical attributes to those individuals, which in turn leads to discrimination.…”
Section: Stereotypingmentioning
confidence: 99%
“…Stereotypes of overweight individuals that have been found include: being lazy; low in competence, ability, and skill; sloppy; more likely to have negative personality traits; lacking selfdiscipline and control; and having poor work habits. Consistent findings of negative stereotypes toward overweight individuals have led a number of researchers to make a connection between weight stereotypes and discrimination in employment settings (e.g., Crocker et al, 1993;Finkelstein, Frautschy Demuth, & Sweeney, 2007;Roehling, 1999)."Fit" Theories. Early theory on stereotyping suggested that negative evaluative outcomes for individuals resulted from the negative stereotypes associated with the groups to which the individuals belonged (e.g., Allport, 1954).…”
mentioning
confidence: 99%